The Effect of Meditation on Blood Pressure Reduction in Hypertension Patients in the Batudaa Pantai Health Center Work Area - Abdul Wahab Pakaya; EuisHerawati Hidayat (PSPP JOURNALS, 2022)
Data, the incidence of hypertension in Gorontalo Regency in 2019 was 14,590 cases. Most hypertensive patients do not control their blood pressure and only treat their disease with traditional medicine. The purpose of this study was to analyze the effect of meditation on reducing blood pressure in patients with hypertension in the working area of Batudaa Pantai Health Center. This study uses a Pre Post Test with Control design with the type of Quasy Experiment research. The population is 67 respondents who suffer from hypertension and live in the working area of Batudaa Pantai Health Center with purposive sampling technique and the number of samples is 30 respondents. The results showed that there was a significant effect in the intervention group with a Mean systolic value of 6,000 mmHg and a Mean diastolic of 6667 mmHg, a control group with a systolic mean of 2.667 mmHg and a Meandiastolic value of 2.667 mmHg where p-value < 0.05. The conclusion in this study is that there is an effect of meditation on reducing blood pressure in patients with hypertension in the working area of Batudaa Pantai Public Health Center.